Bibliometric Analysis of Corporate Social Responsibility Topics in Accounting and Finance - Judijanto, Loso; Utami, Fiesty (Westscience Press, 2025)
This research performs an extensive bibliometric analysis to delineate the conceptual framework and thematic evolution of Corporate Social Responsibility (CSR) research in the domains of accounting and finance. The investigation utilizes Scopus-indexed publications and VOSviewer visualization tools to investigate publication patterns, keyword co-occurrences, prominent authors, institutional collaborations, and country-level networks. The results reveal that CSR is the main research hub, connecting important topics including corporate governance, financial performance, environmental management, sustainability accounting, and integrated reporting. The findings reveal a transition from initial governance- and performance-focused research to contemporary subjects such as materiality, global reporting requirements, and sustainability disclosure frameworks. The collaboration networks show that the US, Europe, China, and Southeast Asia all make important contributions. This shows how CSR scholarship is connected around the world. The study enhances theoretical understanding by elucidating prevailing conceptual frameworks and emphasizing novel intersections between sustainability reporting and financial decision-making. There are also practical consequences for regulators, businesses, and professionals that want to improve CSR integration.